Islamic social enterprises in Bangladesh: Conceptual and institutional challenges - Md. Fazla Mohiuddin (Cogent Business & Management, 2017)
To date, very little attention has been given to Islamic social enterprise although it has huge potential within the context of third sector economy. Addressing this gap, taking Bangladesh as a point of departure, this paper explores how Islamic social enterprise can contribute to enhance the effectiveness of third sector economy. Drawing on lessons from different case studies, it finds that government of Bangladesh should provide a separate legal and regulatory environment for Islamic social enterprise for it to grow in size and scale. In addition to that, the paper came up with three themes which could provide crucial guidelines for Bangladeshi Islamic social enterprise to improve operation and effectiveness. These themes are: leveraging social capital, product and service innovation, and formation of apex institutional bodies. The paper ends with actionable and transparent policy and strategy recommendations for all the stakeholders.
Keywords: 650